Prerequisites for Emergency Laparoscopic Surgery for Colorectal Cancer - Young, Wan Kim (Journal of Surgery Proceedings, 2016)
This practical overview lists prerequisites for emergent laparoscopic colorectal cancer surgery, including team readiness, equipment, and perioperative protocols to optimize patient safety.
Keywords: Emergencies; Laparoscopy; Surgical procedures